Ответ:
Пошаговое объяснение:
(- 3 1/4 +2 1/6)* (-2 2/11) - (-5/6 + 1 3/5) * (-4/5-1,2)= 3 148/165
1)(- 3 1/4 +2 1/6)= -13/4 +13/6= -39/12 + 26/12= -13/12
2) -13/12 * (-24/11) = 26/11
3) (-5/6 + 1 3/5)= -5/6 + 8/5= -25/30 +48/30= 23/30
4) (-4/5 - 1 1/5)= -4/5 - 6/5= - 10/5 = -2
5) 23/30 * (- 2)= -23/15
6) 26/11 -(- 23/15)= 390/165 + 253/165= 643/ 165= 3 148/165
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
(- 3 1/4 +2 1/6)* (-2 2/11) - (-5/6 + 1 3/5) * (-4/5-1,2)= 3 148/165
1)(- 3 1/4 +2 1/6)= -13/4 +13/6= -39/12 + 26/12= -13/12
2) -13/12 * (-24/11) = 26/11
3) (-5/6 + 1 3/5)= -5/6 + 8/5= -25/30 +48/30= 23/30
4) (-4/5 - 1 1/5)= -4/5 - 6/5= - 10/5 = -2
5) 23/30 * (- 2)= -23/15
6) 26/11 -(- 23/15)= 390/165 + 253/165= 643/ 165= 3 148/165